2021
DOI: 10.3390/min11090954
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Semirigorous and Empirical Models Derived Using Data Quality Assessment Methods

Abstract: With the increase in available data and the stricter control requirements for mineral processes, the development of automated methods for data processing and model creation are becoming increasingly important. In this paper, the application of data quality assessment methods for the development of semirigorous and empirical models of a primary milling circuit in a platinum concentrator plant is investigated to determine their validity and how best to handle multivariate input data. The data set used consists o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…On figure 1 it is shown a typical technological scheme of the process of grinding ore during its enrichment, which is widely used in processing plants [22]. Initial ore and water are supplied to the mill, which operates in a closed cycle with hydrocyclones.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On figure 1 it is shown a typical technological scheme of the process of grinding ore during its enrichment, which is widely used in processing plants [22]. Initial ore and water are supplied to the mill, which operates in a closed cycle with hydrocyclones.…”
Section: Resultsmentioning
confidence: 99%
“…On figure 2 it is shown the main notation and variables used in the mathematical model of the sump in the technological chain of the closed grinding cycle [22,30,31]. Q(t) denotes the flows at the corresponding points of the technological process, W is the content of the solid phase of the pulp, M (t) is the mass of material in the technological units at time t. In addition, when modeling the grinding cycle, the following designations were adopted: P (x, t) is the cumulative yield of solid particles whose size is less than x; Xi = ∂P (x,t) ∂x i ∆xfraction of the crushed material, the particle size of which belongs to the size interval i.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned earlier in this paper, the n values can be determined using either linear or non-linear regression analysis, and the method used defines the accuracy of the RR distribution model. The accuracy of this model was determined using the correlation coefficient (R 2 ) [35,46] which showed that general higher R 2 values are obtained when non-linear regression analysis was used. In addition, it was revealed that the estimated n values were significantly different under the same operating conditions after the two methods were applied.…”
Section: Use Of the Non-linear Modelmentioning
confidence: 99%